ANALISIS HUKUM TERHADAP PELAKU AKTIVITAS PIDANA PENCABULAN DAN KEKERASAN ANAK DI BAWAH UMUR (PUTUSAN NO.49/PID.SUS/2019/PN LBB) - Farhana, Farhana; Saputra, Muhammad Fadira; Batubara, Sonya Airini (Legal Standing : Jurnal Ilmu Hukum, 2023)
Often criminal acts occur in human life and that includes their problems. usually this is because of something like their lust that wants a crime. Crimes that can be committed include various kinds of acts of harassment, obscenity and sexual violence. Types of crimes whose actions are in the category of sexual violence such as obscenity have a lot of impact on the victims. The victims besides being harmed they will also experience trauma and high shame. The study that will be carried out uses normative juridical, namely the method used in conducting research in the field of law with steps. This method works by analyzing legal sources in writing and available in the literature. The materials used in this research are laws, research journals, and books that are still relevant to the prevailing problems. This research uses a descriptive approach. where research is based on written rules as they are. Legal research on child abuse has basically been stated in article 76 E of Law no. 35 of 2014 regarding changes to Law NO. 3 of 2002 which deals with child protection. It is clearly stated in article 76 E which reads "Every person is prohibited from committing violence or threats of violence, forcing, deceiving, committing a series of lies, or persuading children to commit or allow obscene acts to be carried out". This case is also listed in the Lubuk Basung Court Decision No. 49/pid.sus/2019/PN LBB which received the result of the decision because the law had reported that the defendant was stating that the defendant was legally proven guilty of carrying out a crime in the form of intercourse with a minor. This violates Article 76 D in conjunction with Article 81 paragraph 1 UURI Number 35 of 2014 regarding changes to Law no. 23 of 2002 regarding child protection.